A Novel SPAST/SPG4 Splice-Site Variant in a Family with Dominant Hereditary Spastic Paraplegia. (29th August 2020) - Robbins, Nathaniel M.; Ozmore, Jillian R.; Winder, Thomas L.; Gonzalez-Alegre, Pedro; Bardakjian, Tanya M.
Abstract : Some causes of spastic paraplegia are treatable and many are not. Diagnostic work-up to determine the etiology can be costly and invasive. Here we report the case of a man with slowly progressive spastic paraparesis. Using a multigene next-generation sequencing (NGS) panel, we identified a novel variant in the consensus splice site of the SPAST gene (exon 13, c.1536G>A, heterozygous), affecting codon 512 of the SPAST mRNA. The observed variant segregated with the disease in four tested family members. In this case, genetic confirmation obviated the need for additional testing such as MRI and lumbar puncture and helped the patient and his family understand his condition and prognosis. We conclude with a brief discussion of the SPG4/SPAST gene and the role of multigene panels in the diagnosis and management of hereditary spastic paraplegia.